Study of the Anti-inflammatory Activity of 2-hydroxy-4-oxo-4-R-2-butenoates of Heterylammonium, which Have an Effect on the Blood Clotting System - F. V. Sobin; N. A. Pulina; S. V. Chashchina; A. V. Starkova; I. P. Rudakova; N. A. Buzmakova (Разработка и регистрация лекарственных средств)
Introduction. The use of anticoagulants is relevant in therapeutic, cardiological, neurological practice, geriatrics, obstetrics and gynecology, as well as in complications associated with COVID-19 infection and vaccination. In-depth studies of additional pleiotropic effects of existing anticoagulants are being conducted. The anti-inflammatory effect of heparins and direct oral anticoagulants was found. Special emphasis is placed on the existing close relationship between coagulation and inflammatory processes. The interaction of anticoagulants with nonsteroidal anti-inflammatory drugs when taken together is actively discussed. The combination of anticoagulant and anti-inflammatory action in one chemical molecule can solve the problem of polypragmasia.Aim. To study the anti-inflammatory activity of promising 2-hydroxy-4-oxo-4-R-2-butenoates of heterylammonium, which have an effect on the blood clotting system.Materials and methods. For further study of anti-inflammatory activity, 2-hydroxy-4-oxo-4-R-2-butenoates of heterylammonium, which have an effect on the blood clotting system, were selected. The anti-inflammatory effect was studied on a model of acute inflammatory edema in mongrel rats of both sexes weighing 180–250 g. The studied compounds were administered intragastrically. Diclofenac sodium and nimesulide substances administered similarly were used as comparison drugs. Acute toxicity of substances that showed activity was studied on white nonlinear mice of both sexes weighing 18–22 g with the definition of LD50.Results and discussion. All the studied 2-hydroxy-4-oxo-4-R-2-butenoates of heterylammonium have anti-inflammatory effects of varying severity. Data on the study of acute toxicity during intragastric administration, allow us to attribute the studied compounds to the 4.5 class of the hazard classification of chemical products.Conclusion. The anti-inflammatory activity of 14 2-hydroxy-4-oxo-4-R2-butenoates of heterylammonium has been studied. Five butanoate have an effect lower than comparison drugs, eight compounds are comparable to the effect of reference drugs, one compound is superior to nimesulide. The studied compounds can be assigned to class 4,5 of the hazard classification of chemical products. Medicinal candidates have been selected for further pharmacological, toxicological and technological study.